Effects of disturbance caused by traditional Spanish rural land use on the regeneration of Cytisus multiflorus - Fernández-Santos, B.; Gómez-Gutiérrez, J. M.; Moreno-Marcos, G. (Applied Vegetation …, 1999)
. Cytisus multiflorus is a leguminous matorral shrub native to the NW Iberian Peninsula, where it is one of the most important species in the extension of matorral at the expense of set-aside agricultural land. Dehesas have traditionally been used for extensive livestock raising and matorral was periodically burnt, cut or pulled out. The two latter practices are now out of use. However, burning is more frequent than in the past. The effects of fire, cutting, and pulling out of C. multiflorus on its regeneration was studied in order to ascertain whether the presently increasing distribution of the species relates to firestimulated regeneration or to the reduction of other traditional practices. Three years after treatment two sets of parameters were determined: 1. Plant origin: seedlings and different ramet types ( ramets = resprout clumps), density, weight, and biomass as well as the percentage of resprouting. 2. Seed persistence at various soil depths. The possible mechanisms of breaking dormancy and plant emergence in different years after fire were studied in other experiments. The results suggest that the regeneration mechanism in C. multiflorus is stimulated by fire, but it is not an exclusive relationship. Stimulation occurs also after other disturbances leading to the total elimination of aerial biomass. The present expansion of the species does not appear to result from the abandonment of some traditional practices, such as cutting or pulling out, but from frequent fires (resulting in aerial-biomass elimination).
Keywords: Cutting; fire; Mediterranean shrubland; Pull-out; Ramet; seed bank; Seedling